The influence of consumer anthropomorphism on attitudes towards artificial intelligence trip advisors. (September 2020) - Martin, Brett A.S.; Jin, Hyun Seung; Wang, Di; Nguyen, Han; Zhan, Kai; Wang, Ying Xian
Abstract: This research note investigates how consumers' individual differences are associated with their attitude towards trip advice that has been curated by artificial intelligence (AI). Individual difference factors (anthropomorphic tendency, need for cognition, disillusionment toward marketing, life satisfaction) and variables such as smart phone usage were correlated with attitude towards AI-curated reviews (AAICR ). A survey of 212 individuals from Taizhou, China found that anthropomorphic tendency, need for cognition, and smart phone usage were positively associated with AAICR . When controlling for the effect of need for cognition and smart phone usage, the effect of anthropomorphism on attitudes was still robust. Disillusionment toward marketing and life satisfaction were not associated with AAICR . The results contribute to the tourism literature by showing the effect of anthropomorphism on AAICR . Tourism practitioners who wish to inspire consumers with AI-curated destination reviews should target consumers with a high anthropomorphic tendency.